Exploring the impact of unpaid domestic and care work on academic productivity and career advancement in Sri Lankan universities - Wijeyesekera, R.; Thilakarathna, K.A.A.N. (University of Colombo, 2025)
Unpaid care and domestic work (UCDW) consume significant time and energy, yet remain largely undervalued and rarely recognized within economic or institutional frameworks. Deeply entrenched gender norms, coupled with family expectations and obligations, disproportionately assign this burden to women, restricting their right to development and equal participation in society. Globally, UCDW has been recognized as a structural barrier to women’s access to employment, career advancement, and leadership roles. A 2017 study found that over 67 percent of Sri Lankan women of working age identified UCDW as the primary reason for their inability to participate in paid work, despite their willingness to do so. The higher education sector offers a telling example of this imbalance. For women academics, the multidimensional nature of UCDW including household management, caregiving responsibilities, and cultural expectations limits research productivity, delays promotions, and reduces representation in leadership, thereby constraining their professional growth and weakening the capacity of Sri Lanka’s higher education system to fully harness its talent. While universities have adopted certain mechanisms such as flexible work schedules, maternity leave, and limited childcare facilities,...
Keywords: Unpaid care and domestic work; Gender equality and higher education